1978
DOI: 10.1038/bjc.1978.80
|View full text |Cite
|
Sign up to set email alerts
|

Complement Receptor Subtypes C3b and C3d in Lymphatic Tissue and Follicular Lymphoma

Abstract: Summary.-To substantiate the origin of follicular (nodular) lymphoma cells from germinal-centre cells, the lymphoma cells from 7 patients with follicular lymphoma and from 9 tonsils and 2 lymph nodes were studied for the presence and distribution of complement-receptor subtypes (i.e., the receptors for C3b and C3d). It was found that erythrocytes coated with antibodies and C3d (EAC3d) adhered exclusively to germinal centres, whereas erythrocytes coated with antibodies and C3b (EAC3b) adhered to germinal centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The presented data on complementreceptor subtypes are interesting in connection with our recent observations on the occurrence and distribution of complement receptor subtypes in follicular hyperplasia (Stein et al, 1978b). We found that EAC(3d usually adhered to germinal centres and the follicular mantle, whereas EAC3b adhered not only to germinal centres and the follicular mantle, but also to parafollicular areas and, in many instances, to interfollicular areas, but spared the T-dependent paracortical zone.…”
Section: Morphological Findingssupporting
confidence: 76%
See 1 more Smart Citation
“…The presented data on complementreceptor subtypes are interesting in connection with our recent observations on the occurrence and distribution of complement receptor subtypes in follicular hyperplasia (Stein et al, 1978b). We found that EAC(3d usually adhered to germinal centres and the follicular mantle, whereas EAC3b adhered not only to germinal centres and the follicular mantle, but also to parafollicular areas and, in many instances, to interfollicular areas, but spared the T-dependent paracortical zone.…”
Section: Morphological Findingssupporting
confidence: 76%
“…Those investigators showed that erythrocyte-antibody-complement complexes (EAC) prepared with whole mouse serum (EACmouse) as complement source adhered exclusively to germinal centres. Recently, our research group analysed the presence and distribution of D)r H. Steiin, Institute of Patliology, University of the complement-receptor subtypes (receptors for C3b and C3d) in reactive lymphoid tissue (Stein et al, 1978b). We found that GCC bear both complement-receptor subtypes.…”
mentioning
confidence: 92%
“…DURING RECENT YEARS non-Hodgkin lymphomas (NHL) have been characterized by immunological methods in a number of laboratories (Aisenberg & Long, 1975;Bloomfield et al, 1976;Braylan et al, 1975;Brouet et al, 1975;Lukes et al, 1978;Stein et al, 1978;Habeshaw et al, 1979). Staining of lymphocyte membrane antigens (with antisera) in formalin-fixed paraffin-embedded tissues has yielded variable results (Braylan & Rappaport, 1973;Taylor, 1978).…”
mentioning
confidence: 99%
“…Thus most of the published studies have been carried out on suspensions of cells obtained from teased lymph nodes, a technique which is better suited to the requirements of membranemarker analysis. These studies have demonstrated that most lymphomas are of B-lymphoid origin and express "monoclonal" surface-membrane immunoglobulin (SmIg; with K or A light chain) and that complement receptors, Fc receptors and the capping characteristics of SmIg distinguish histologically distinct types of B lymphomas (Jaffe et al, 1974;Stein et al, 1978;Habeshaw et al, 1979). A small proportion of lymphomas have been shown to be of T-cell origin (Lukes & Collins, 1974;Bloomfield et al, 1976;Koziner et al, 1977;Stein et al, 1976;Waldron et al, 1977).…”
mentioning
confidence: 99%
See 1 more Smart Citation